Glycaemic control among diabetic patients in Medical Ward, Hospital Selayang / Siti Nur Fadzilah Muhsain ... [et al.] - Muhsain, Siti Nur Fadzilah; Othman, Mohd Izani; Noordin, Noor Hazarina; Mohd Ali, Salmiah (2011)
Inadequate glycaemic control remains one of the problems that need to be addressed by health practitioners. Increasing complexity in the diabetes medication regimen as well as the need for treatment for other co-morbidities among the diabetics patients have led to poor glycaemic control. This prospective study was conducted to assess the good and inadequate glycaemic control among type 2 diabetic patients in Medical Ward, Selayang Hospital and patients’ adherence to prescribed diabetes treatment. Fifty one diabetic patients who fulfilled the inclusion criteria participated in the study. Data were collected trough questionnaires and patients’ medical profile. Statistical Package for the Social Science (SPSS) Version 12.0 was used in analyzing the data. Majority of the patients were Malays and Indians (35%) and females (56.9%) with mean age 59.9 ± 13 years. 45.1% of the patients completed secondary school education and 47% of the patients were with more than 10 years of diabetic duration. 88.2% of the patients showed inadequate glycaemic control. The mean HbAlc level was 8.8±2.2%. Females, elderly, Malays, patients with more than one antidiabetic agent and more than one diabetic complications were the characteristics of patients with highest percentage of inadequate glycaemic control although no statistical difference was reached. Adherence level was poor with 54.9% of the patients were non-adherent to their prescribed antidiabetic treatment. The study showed that glycaemic control and adherence level among type 2 diabetic patients in Malaysia is still inadequate and at a poor state. Frequent review of the glycaemic control and adherence level together with patient counseling may increase achievement of goal of antidiabetic therapy thus improved patients’ health related quality of life.